The Complete Chloroplast Genome of Wild Rice (Oryza minuta) and Its Comparison to Related Species - Asaf, Sajjad; Waqas, Muhammad; Khan, Abdul L.; Khan, Muhammad A.; Kang, Sang-Mo; Imran, Qari M.; Shahzad, Raheem; Bilal, Saqib; Yun, Byung-Wook; Lee, In-Jung (Frontiers in Plant Science, 2017)
Oryza minuta, a tetraploid wild relative of cultivated rice (family Poaceae), possesses a BBCC genome and contains genes that confer resistance to bacterial blight (BB) and white-backed (WBPH) and brown (BPH) plant hoppers. Based on the importance of this wild species, this study aimed to understand the phylogenetic relationships of O. minuta with other Oryza species through an in-depth analysis of the composition and diversity of the chloroplast (cp) genome. The analysis revealed a cp genome size of 135,094 bp with a typical quadripartite structure and consisting of a pair of inverted repeats separated by small and large single copies, 139 representative genes, and 419 randomly distributed microsatellites. The genomic organization, gene order, GC content and codon usage are similar to those of typical angiosperm cp genomes. Approximately 30 forward, 28 tandem and 20 palindromic repeats were detected in the O. minuta cp genome. Comparison of the complete O. minuta cp genome with another eleven Oryza species showed a high degree of sequence similarity and relatively high divergence of intergenic spacers. Phylogenetic analyses were conducted based on the complete genome sequence, 65 shared genes and matK gene showed same topologies and O. minuta forms a single clade with parental O. punctata. Thus, the complete O. minuta cp genome provides interesting insights and valuable information that can be used to identify related species and reconstruct its phylogeny.